Regulations of the administration and a necessary redefinition of urgent contentious-administrative proceedings - Jiménez Vivas, Javier Eduardo (2022)
The contentious-administrative proceeding is an ordinary procedural instrument designed to offer procedural protection against the actions of the administrative authorities, as well as to legally control their functions. Their urgent nature serves to offer said protection and carry out said control, in terms of the de facto actions and omissions of the Administration. However, our legislation does not consider those cases in which the de facto action is produced with respect to the provisions established in a rule, or when the behavior of the administrative authority omits the provisions of a rule. We are facing two cases in which the constitutional principle of inter-unit control and the constitutional right to effective legal protection are affected.